Analysis of Digital Presence Information Systems in Minimizing the Potential for Fraud for Employee Discipline in Schools - Teguh Aljauza; Franciskus Antonius Alijoyo (Indonesian Journal of Primary Education, 2023)
This research aims to analyze the effectiveness of the digital presence information system in minimizing the potential for fraud in order to increase employee discipline. The main focus of the research is on independent variables, including school registration in the application, teacher account management by school admin, teacher device registration, QR device registration by school admin, and QR regeneration every 10 seconds. The dependent variables observed include the effectiveness of the attendance system, employee discipline, the reliability of GPS location and IP address, the impossibility of transferring accounts, and the impossibility of QR duplication. This research uses a quantitative research method with a survey approach using a questionnaire as a data collection instrument. The sample of respondents was 30 schools as application users. Analysis of testing the validity and reliability of instruments using SmartPLS 4 software. It is hoped that the research results will provide an in-depth understanding of the effectiveness of the digital presence information system in the context of employee discipline in the school environment. It is hoped that the findings from this research can make an important contribution to the development of digital attendance information systems in schools. It is hoped that the practical implications of this research will help schools improve the effectiveness and security of digital attendance systems. Apart from that, it is hoped that the benefits of this research can contribute to literature related to employee discipline management in the educational context. This research provides new insights into the application of digital attendance technology in schools, highlighting key aspects that influence system effectiveness and security. Thus, it is hoped that this research can become a basis for further research and provide direction for the development of digital attendance information systems in educational institutions.